Communication between cultures - Samovar, Larry A.; Porter, Richard E. (Belmont, CA : Wadsworth, 2001)
Communication and culture. The influence of culture. From theory to practice. Knowledge into action.
Keywords: Intercultural communication; Intercultural communication; Communication and culture